2011
DOI: 10.1097/prs.0b013e3181fed595
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Osseointegrated Auricular Reconstruction

Abstract: The authors present long-term results showing both success and complications of the osseointegrated prosthetic ear reconstruction for a variety of different etiologies and age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Despite concerns about the psychosocial health of patients with OPAR, published reports have demonstrated very satisfied patients who wear their prosthesis for more than 10 hours per day and consider the prosthesis as a part of them. [11][12][13][14][15] The clinical outcomes of an auricular prosthesis may be evaluated by considering implant success, prosthesis success, and patient satisfaction ( Table 4). The implant success rate in our patient group was 89%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite concerns about the psychosocial health of patients with OPAR, published reports have demonstrated very satisfied patients who wear their prosthesis for more than 10 hours per day and consider the prosthesis as a part of them. [11][12][13][14][15] The clinical outcomes of an auricular prosthesis may be evaluated by considering implant success, prosthesis success, and patient satisfaction ( Table 4). The implant success rate in our patient group was 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were good candidates for autogenous ear reconstruction but elected for OPAR were excluded. Our institution's method of auricular osseointegration has been described previously 11 and consists of 2 stages: placement of 2 or more titanium implants directly into bone (Phase 1) followed by implant exposure 3 to 6 months later for connection of load-bearing abutments (Phase 2). Under ideal circumstances, both phases may be done at 1 sitting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Survival rates of auricular osseointegrated implants are excellent as the overall failure rate of osseointegration in the mastoid region was as low as 2% in some larger studies. 31 Further studies have shown that craniofacial rehabilitation is safe and predictable with high survival rates and low soft tissue reactions with close follow-up. 32 In particular, patients report satisfaction with osseointegrated maxillofacial prostheses.…”
Section: Discussionmentioning
confidence: 98%
“…Wilkes and Wolfaardt [6] list the indications used by their team for prosthetic reconstruction: cancer resection, radiotherapy, absent lower half of the ear, severely compromised tissue, patient preference, failed autogenous reconstruction, potential craniofacial anomaly, poor condition and high operative risk. In contrast, some scholars think the most ideal indication for reconstruction to be an acquired total or subtotal auricular defect, most often traumatic or ablative in origin [7,8]. …”
Section: Introductionmentioning
confidence: 99%